(untitled) (American Journal of Business Management, Economics and Banking, 2023)
This study aims to clarify the repercussions of the Russian-Ukrainian war on the rentier economies in general, and Iraq in particular - as its economy depends on more than 90% on oil revenues - and to review the mechanisms of confronting it, to reduce its negative effects and enhance its positive effects. The study relied on the descriptive analytical approach to achieve its objectives, by referring to the secondary data issued by the official authorities in Iraq. The study reached a number of conclusions, the most important of which are; the cumulative errors in the Iraqi financial policies for the years after 2003, have widened the gap between economic balance & imbalance, and devote reliance on oil revenues in financing operational budgets without development. The study reached several conclusions, the most important of which are; The Russo-Ukrainian war has significantly changed the global economic order. It also contributed to the increase in the prices of exported crude oil by a greater percentage than the increase in the prices of some imported basic commodities. Several recommendations were formulate, the most important of which are; the differences in prices and the quantities of exported crude oil should be used to develop the Iraqi economy and rationalize domestic consumption.